After the deluge: Appraising the 1970 Mufulira mine disaster in Zambia (Historia, 2021)
This article endeavours to position the Mufulira mine disaster in the wider historiography of mining in post-colonial Zambia. In the early hours of 25 September 1970, about two million tonnes of water, and slimes cascaded into the main working area of the Mufulira copper mine on the Zambian Copperbelt. It choked the mine's main and intermediate haulages, and put three incline shafts, an ancillary crusher, and pumping stations out of action. This deluge, the worst mine disaster in the country's mining history, resulted in the death of 89 miners and had the subsequent socio-economic effect of having to resettle their widows and orphans. The cataclysm also led to a cut, by as much as 50 per cent, of the nation's copper production, its main foreign exchange earner. The resultant reduction in government revenue generation due to a decline in copper production had a severe impact on the nation's fiscus. But most importantly, this tragedy occurred at a time of serious socio-political challenges in the newly independent state of Zambia. While the incident at Mufulira was costly to shareholders, the state, and the affected families, it also became a blessing in disguise because its aftermath set new standards in mine safety on the Copperbelt as well as in the rest of the mining industry.